Genome-wide identification of bZIP transcription factors and their responses to abiotic stress in celery. Issue 1 (1st January 2019) - Yang, Qing-Qing; Feng, Kai; Xu, Zhi-Sheng; Duan, Ao-Qi; Liu, Jie-Xia; Xiong, Ai-Sheng
Abstract: Celery ( Apium graveolens L.) is one of the most important vegetables in the Apiaceae family, rich in nutrients and widely grown around the world. bZIP transcription factors family plays an important role in the transcription regulation of plant growth and development, as well as adaptation to the external environment. In this paper, 62 bZIP family transcription factors were screened and identified based on the whole genome sequence of celery. The bZIP proteins of celery and Arabidopsis thaliana were divided into 10 subfamilies according to the phylogenetic tree. Phylogenetic and evolutionary analysis showed that the number of bZIP family members gradually expanded from lower plants to higher plants during the long evolution process. Based on the homology of celery and A. thaliana bZIP genes, the interaction network between celery bZIP transcription factors and other proteins in the genome was constructed, and the correlation data of protein interaction were also obtained. The expression profiles of 12 selected AgbZIP genes were detected and analyzed under abiotic stress treatments and different tissues using RT-qPCR. The results showed that AgbZIP can respond to high temperature, low temperature, drought, and high salt stress.